A Comparative Study of Primary School Teachers’ Views about Dyslexia in the UK and Greece - Kostopoulou, Rodopi (2013)
The present study is a comparative research on primary teachers’ understanding of dyslexia in the UK and Greece. More specifically, aim of the research was to investigate primary teachers’ knowledge about dyslexia, their attitudes towards students with dyslexia, the procedures they follow for the identification of dyslexic students and the way teachers respond to their learning and emotional needs, in both countries. The sample consisted of six primary teachers (three English and three Greek), currently working in schools. Data were interpreted in comparison to previous research findings, in the context of the educational systems of the two countries. Findings illustrated that teachers from England and Greece have a common understanding of dyslexia, holding a positive view for dyslexic students’ inclusion. However, teachers from both countries feel unsupported and that they lack knowledge about dyslexia. Concerns are raised on teachers’ preparedness to identify and offer research-driven response to dyslexic students’ needs. Thus, some implications for practice are discussed.